Comparison of the Mechanical Properties and Approach to Numerical Modeling of Fiber-reinforced Composite, High-Strength Steel and Aluminum - Abdulqadir, Samer Fakhri; Alaseel, Bassam Hamid; Sameer, Jamal Oudah (Journal of Engineering and Technological Sciences, 2024)
The performance of carbon fiber reinforced polymer (CFRP) composite materials under quasi-static and high strain rate loading can be predicted with a high level of accuracy using the non-linear finite element analysis (FEA) method. Experimental validation tests under uniaxial tensile loading have shown a good correlation with FEA predictions for thermoset polymer composites, using commercially available epoxy resin MTM710 with carbon fiber reinforcement and for comparative tests on DP600 steel and aluminum alloys (AC170 and 5754 series). The physical and numerical results comparison of composite, aluminum, and high-strength steel indicates that the composite may be used as an alternative to aluminum and high-strength steel since the composite was shown to have almost the same strength as steel and higher strength than aluminum with the advantage of being lightweight and possessing similar mechanical behavior under quasi-static conditions. The results demonstrated that the strain rate range used did not significantly affect the strength of the composite materials. The selection of materials can be optimized reliably by FEA based on mechanical properties, cost, and weight. This will significantly reduce the new product introduction timescale, which is essential for the wider use of polymer composites for structural applications, especially in the automotive industry.